The Orphan Army - Maberry, Jonathan (New York : Simon & Schuster Books for Young Readers, 2015)
In the future, bug-like aliens are taking over Earth and young Milo Silk learns through dreams and strange encounters that there are other, ancient monsters on the planet that are also threatened by the aliens, and that he may be the hero destined to lead his friends in saving the universe.